THE SIGNIFICANCE OF FOREIGN JOINT VENTURES IN THE DEVELOPMENT OF SIRDARYA REGION DURING THE YEARS OF INDEPENDENCE - Tursunova Mahliyo Sarvar qizi (Western European Studies, 2026)
This scientific article analyzes the role and significance of foreign joint ventures in the socio-economic development of the Syrdarya region during the period following the independence of the Republic of Uzbekistan. The study examines the legal foundations for attracting foreign investments and assesses the impact of joint venture activities on industry, agriculture, employment, and export potential based on statistical and regulatory legal sources. The research findings indicate that foreign joint ventures are among the key factors of regional development in the Syrdarya region.
Keywords: foreign investment; joint ventures; regional development; industrialization